Extracellular vesicles isolated from Toxoplasma gondii induce host immune response. (1st August 2018) - Silva, Valeria Oliveira; Maia, Marta Marques; Torrecilhas, Ana Claudia; Taniwaki, Noemi Nosomi; Namiyama, Gislene Mitsue; Oliveira, Katia Cristina; Ribeiro, Kleber Silva; Toledo, Maytê dos Santos; Xander, Patricia; Pereira‐Chioccola, Vera Lucia
Summary: This study established a protocol to purify Toxoplasma gondii tachyzoite microvesicles and exosomes, called as extracellular vesicles (EVs). In addition, the investigations were conducted to determine the kinetic of EV release by tachyzoites and whether EV proteins are able to modulate the host immune response. The particle size and concentration released by tachyzoites in culture medium at different incubation‐period were characterized by nanoparticle tracking analysis. Tachyzoites (1 × 10 6 ) released around 4.37 ± 0.81 × 10 8 EVs/mL/h, with size varying between 138.2 and 171.9 nm. EVs released into the medium were purified by gel‐exclusion chromatography and screened by ELISA, using a pool of human positive sera for toxoplasmosis. EV‐fractions contained high concentration of proteins, and EVs were analyzed by scanning and transmission electron microscopies. Tachyzoites released EVs into the culture medium throughout all membrane surface, and these vesicles contain small RNAs/miRNA. Pooled sera from chronically infected human or mice (infected with 2 different T. gondii strains) recognized distinct EV electrophoretic patterns in immunoblotting. T. gondii EVs significantly induced IL‐10, TNF‐α and iNOS in murine macrophages. In conclusion, this study shows that T. gondii secrete/excrete EVs (microvesicles and exosomes) contain miRNA and they were immunologically recognized by host immune response.